1997
DOI: 10.1146/annurev.physchem.48.1.711
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Dynamics of Electrons on Surfaces and at Interfaces

Abstract: Two-photon photoemission is a promising new technique that has been developed for the study of electron dynamics at interfaces. A femtosecond laser is used to both create an excited electronic distribution at the surface and eject the distribution for subsequent energy analysis. Time- and momentum-resolved two-photon photoemission spectra as a function of layer thickness fully determine the conduction band dynamics at the interface. Earlier clean surface studies showed how excited electron lifetimes are affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
209
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(216 citation statements)
references
References 84 publications
6
209
1
Order By: Relevance
“…It is only recently that advances in the time-resolved two-photon photoemission (TR-2PPE) allowed us to study energies and lifetimes of IPRs with high n. 39,40 Theoretical studies of the lifetimes of IPRs reported so far addressed resonant decay into the bulk treated with the one-electron wave-packet propagation (WPP) technique. [35][36][37][38] Good agreement with the experimental data 6,8,30,36,37,42 has been obtained, allowing detailed discussion of the role of the resonant one-electron tunneling into the substrate.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…It is only recently that advances in the time-resolved two-photon photoemission (TR-2PPE) allowed us to study energies and lifetimes of IPRs with high n. 39,40 Theoretical studies of the lifetimes of IPRs reported so far addressed resonant decay into the bulk treated with the one-electron wave-packet propagation (WPP) technique. [35][36][37][38] Good agreement with the experimental data 6,8,30,36,37,42 has been obtained, allowing detailed discussion of the role of the resonant one-electron tunneling into the substrate.…”
Section: Introductionsupporting
confidence: 58%
“…39 Further, we apply our method to study the energies and lifetimes of IPRs at the Y point on Cu(110). Indeed, most of the reported experimental 6,8,11,30,36,37,[39][40][41][42][46][47][48][49][50] and theoretical 35,37,38,[43][44][45][48][49][50][51] studies of energies and lifetimes of image potential states and resonances at metal surfaces are restricted to the vicinity of the point of the surface Brillouin zone. The energies of IPSs near the surface Brillouin zone boundary were measured only in a few works.…”
Section: Introductionmentioning
confidence: 99%
“…The image state series persists and becomes less bound with increasing thickness of dielectric layers on Ag(111) 5 as shown in the TPPE spectra taken at 0°emission ( Figure 3A). 20 The change in binding energy correlates to a layerby-layer evolution of the surface potential ( Figure 3B).…”
Section: Electron Tunneling At Metal-alkane Interfacesmentioning
confidence: 87%
“…Several models have been used to describe the decoupling of image-potential states by spacer layers. The basic physics is already contained in simple dielectric continuum descriptions of the adlayers [270]. The main parameters that determine the amount of decoupling are the thickness of the layer and the position of the affinity level, i.e.…”
Section: Decoupling By Spacer Layersmentioning
confidence: 99%
“…In a simple tunneling picture they correspond to the width and height of a barrier and determine the penetration of the wave function [260,267]. In a more realistic description, the modification of the image potential inside and outside of the layer due to its polarizability is also taken into account [263,270,271]. If the energy levels of the image-potential states become degenerate with the conduction band of the adlayer, as it is the case for the n ¼ 2 state and the rare gases Xe and Kr, the wave function of the states penetrate the layer.…”
Section: Decoupling By Spacer Layersmentioning
confidence: 99%